Effectiveness of myofascial release on balance and flexibility in sepak takraw players - Singh, Mallisah Kaur Inderjit (2018)
Myofascial release is an inexpensive and accessible method which allows the individual to maintain their flexibility and potentially release the player‟s fascia tightness anywhere and anytime. The present study aims to determine if myofascial release would improve the flexibility and balance among sepak takraw players. Twenty-three (N=23) male participants (mean age: 14.70 ± 2.69 years; height: 142.48 ± 12.40; weight: 46.70 ± 9.60 and BMI: 22.62 ± 2.49) who has tightness of their hamstring, quadriceps and calf muscles participated in the study. Participant‟s flexibility of the three muscle groups and balance were measured by using goniometer and balance foam. The intervention was done for three sessions with a two days gap in between the days; and a pre-post measurement within each session. The finding from this current study when measured using one-way repeated measure ANOVA showed no significant difference in flexibility of the right and left hamstring, quadriceps and calf muscle (p>0.05) in each session. In addition, balance result on firm and foam surface also showed no significant difference (p>0.05). However, the results showed a significant difference in between each pre-post‟s day session (i.e., within the same day session). The flexibility of hamstring, quadriceps and calf muscle showed a highly significant difference (p<0.001) during each session and over the right and left leg. Furthermore, the balance on firm surface did not show a significance difference (p>0.05). In contrast, the balance on the foam surface showed a significance difference (p<0.001). In summary, the study has found that the effect of myofascial release does not last more than two days (48 hours). However, MFR can be performed for a short term effect on the required players during games rest interval or in between games (i.e., before the next game start) within the same day.